Does the presence of neuropathic pain affect the outcomes of the interlaminar epidural steroid injection for cervical disc herniation? A prospective clinical study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Epidural steroid injections (ESI) are commonly performed for the treatment of chronic cervical disc herniation (CDH). Although they are considered to be effective for both nociceptive and neuropathic types of pain, there is a lack of data regarding the impact of neuropathic pain (NP) and nociceptive pain components on treatment outcomes. The aim of this study is to compare the effectiveness of interlaminar epidural steroid injection (ILESI) between patients with predominantly NP and nociceptive pain due to CDH. Sixty five participants were initially included in the study and assessed by numeric rating scale (NRS), neck pain and disability scale (NPDS), short form-12 (SF-12), and self-reported Leeds assessment of neuropathic symptoms and signs (S-LANSS) pain scale at baseline and 1 month, 3 months, 6 months after ILESI. All patients were evaluated at 1st month and 3rd month follow-up periods while 54 of patients achieved to complete 6th month follow-up. There were significant improvements in all outcome measures for all time periods when compared with the pre-intervention scores. At baseline 24 (36.9%) of patients had predominantly NP in accordance with S-LANSS pain scale. The ratio of NP predominant patients reduced to 7.6% at 1st month, 12.3% at 3rd month, and 12.9% at 6th month with a significant difference for each follow-up period when compared with the baseline. Although all NRS and NPDS scores at baseline were significantly higher in patients with NP, improvement was significant at all follow-up periods in both groups. Minimal clinically important change in NRS was observed in >75% of patients at 1st, 3rd, and 6th month in both groups. The results of this study showed that NP is present in one-third of the patients suffering from neck and radiating arm pain due to CDH and cervical ILESI is an effective treatment approach for both neuropathic and nociceptive components of pain. Clinical Trials Registration Number: NCT04235478
Keywords: disc herniation; interlaminar epidural steroid injections; neck pain; neuropathic pain; LOW-BACK-PAIN; NECK PAIN; LEEDS ASSESSMENT; DOUBLE-BLIND; RELIABILITY; PREVALENCE; DISABILITY; SYMPTOMS; VALIDITY; QUALITY